Ice Princess - Fywell, Tim (Pasig City : Viva Video, 2005)
From Walt Disney Pictures, the studio that brought you The Princess Diaries, ICE PRINCESS is a hilarious and heartwarming coming-of age comedy everyone will love! Though she longs to become a graceful champion figure skater, gawky Casey (MIchelle Trachtenberg) is only a brainy misfit with a strong-willed mother (Joan Cusack) pushing her towards a top university. But when Casey uses her head and follows her heart, she'll find herself transformed and laugh-packed story your family will flip for!